CRISPR/Cas9-induced modification of the conservative promoter region of VRN-A1 alters the heading time of hexaploid bread wheat - Miroshnichenko, Dmitry; Timerbaev, Vadim; Klementyeva, Anna; Pushin, Alexander; Sidorova, Tatiana; Litvinov, Dmitry; Nazarova, Lubov; Shulga, Olga; Divashuk, Mikhail; Karlov, Gennady; Salina, Elena; Dolgov, Sergey (Frontiers in Plant Science, 2022)
The vernalization-related gene network plays an important role in regulation the transition from the vegetative to reproductive phase in cereals to ensure the optimal reproduction in temperate climate. In hexaploid bread wheat (Triticum aestivum L.), the spring growth habit is associated with a presence of at least one dominant loci of VERNALIZATION 1 gene (VRN-1), which usually differs from recessive alleles by mutations in regulatory sequences of the promoter or/and the first intron. VRN-1 gene is a key regulator of floral initiation; various combinations of dominant and recessive alleles, especially VRN-A1 homoeologs, determine the differences in the timing of wheat heading/flowering. In the present study we attempted to expand the types of VRN-A1 alleles by the CRISPR/Cas9 targeted modification of promoter sequence. Several mono- and biallelic changes were achieved within 125-117 bp upstream sequence of the start codon of recessive vrn-A1 gene in plants of semi-winter cv. ‘Chinese Spring’. New mutations stably inherited in next progenies and transgene-free homozygous plants carrying novel VRN-A1 variants were generated. Minor changes of promoter sequence, such as one to four nucleotide insertion/deletion had no effect on the heading time of plants, while the CRISPR/Cas9-mediated eight-base deletion between -125 bp and -117 bp of vrn-A1 promoter shortened the time of head emergence up to 2-3 days. Such a growth habit was constantly observed in homozygous mutant plants under non-vernalized cultivation using different long day regimes (16, 18, or 22 hrs), while the cold treatment (from two weeks and more) completely leveled the effect of eight base deletion. Importantly, that the achieved alteration has no negative effects on main yield characteristics compared to wild-type plants. Our results demonstrate the potential to manipulate heading time of wheat through targeted editing of promoter sequence of VRN-A1 gene on an unchanged genetic background.